Life assessment of welded INCONEL 718 at high temperature - Tanner, David W. J. (2009)
The overall aim behind this work was to gain and apply an understanding of the mechanical effects of welding, in order to mitigate distortions that had previously hampered uniaxial testing of tungsten inert gas (TIG) butt-welded, thin-section, nickel-base superalloy INCONEL 718 (IN718). With this aim achieved, better test data could be obtained, leading to more reliable material data for IN718 welds, which can be used for more accurate life assessments for shell structures and components.